2010
DOI: 10.1111/j.1600-051x.2010.01649.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of Aggregatibacter actinomycetemcomitans serotypes and the JP2 clone in a Greek population

Abstract: a. actinomycetemcomitans serotype b was not statistically correlated with periodontal disease in the investigated sample and the utility of microbiological testing before antimicrobial administration is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 52 publications
2
27
1
Order By: Relevance
“…As showed by several authors [9,10,17,18] the distribution pattern of A. actinomycetemcomitans serotypes varies greatly depending on the periodontal status of the allocated population and the country where the study takes place. Up to now, in Brazil, as well as in Latin America, no study had recruited a considerable number of subjects showing plaque samples positive for A. actinomycetemcomitans, and a diversity of periodontal conditions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As showed by several authors [9,10,17,18] the distribution pattern of A. actinomycetemcomitans serotypes varies greatly depending on the periodontal status of the allocated population and the country where the study takes place. Up to now, in Brazil, as well as in Latin America, no study had recruited a considerable number of subjects showing plaque samples positive for A. actinomycetemcomitans, and a diversity of periodontal conditions.…”
Section: Discussionmentioning
confidence: 96%
“…The authors also observed that serotype a was more frequently detected than serotypes b, d, e, and f. Non-typeable strains were either not detected or were relatively infrequent in the examined population. Sakellari et al [10], while investigating the prevalence and distribution of different A. actinomycetemcomitans serotypes in Greek subjects, observed that serotype b was not statistically correlated with periodontal disease and that no clear predominance of A. actinomycetemcomitans serotypes was observed in non-periodontitis, periodontitis and periodontitis at supportive periodontal treatment patients. In the same year, our group investigated the distribution of A. actinomycetemcomitans serotypes in Brazilian subjects diagnosed with chronic periodontitis.…”
Section: Introductionmentioning
confidence: 98%
“…Available data indicate that the geographic distribution of serotypes is not uniform (6,32,33). The distribution pattern of A. actinomycetemcomitans serotypes varies greatly depending on the periodontal status of the allocated population and the country where the study takes place (22,26,27,32,33). …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that patients are usually infected by only one serotype and colonization is stable over time (28,30), however occasional individuals are colonized with two or three serotypes (31,33,35). Most authors reported frequencies of multipleserotype infection up to 20% (22,27,31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence of aggressive periodontitis amongst adolescents in Morocco who do not have the JP2 clone (Rylev et al 2011), and the finding of the JP2 clone in a Caucasian mother and daughter in Sweden who have no disease (Claesson et al (2011), indicate that carriers do exist in Caucasians and that other serotypes may be associated with disease in African populations. 62.7 18 7.7 57.7 0 7.1 9.4 Vietnamese Finish (Holtta 1994) Serotypes a and b are prevalent in Europeans while serotype c is prevalent in Asian and Mediterranean groups (Table 2 and Sakellari et al, 2011). Cortelli et al, (2005) recommended that serotype b be used as a diagnostic marker for aggressive periodontitis since they found a high prevalence of the JP2 clone in a Brazilian population.…”
Section: Gene Expressionmentioning
confidence: 99%